UPAYA MENANGGULANGI “INVESTASI BODONG” DI INTERNET - Angga Primantari, A. A.; Sarna, Kadek (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 03, Juni 2014)
By using normative research methods, this paper probe about "bulging investment" which often happens in the community. Bulging here means companies or goods that are bulging or both. How about investing online setting and knowing attempt to cope with "bulging investment" are the goal in this paper. In Indonesia, the setting of the need for certification and clear information about the goods, contract terms in investing in the Internet are listed in Law Number 11 Year 2008 on Information and Electronic Transactions. Because of the rampant cases of "Investment bulging", as those who invest should be careful and meticulous as the response to the "investment bulging" on the internet.
Keywords: “bulging investment”, prevention